Managing Rivers for Multiple Benefits–A Coherent Approach to Research, Policy and Planning - Tickner, David; Parker, Helen; Moncrieff, Catherine R.; Oates, Naomi E. M.; Ludi, Eva; Acreman, Mike (Frontiers in Environmental Science, 2017)
Rivers provide water for irrigation, domestic supply, power generation and industry as well as a range of other ecosystem services and intrinsic and biodiversity values. Managing rivers to provide multiple benefits is therefore foundational to water security and other policy priorities. Because river flow is often insufficient to meet all needs fully, water management experts have acknowledged the need for trade-offs in river management. Ecosystem scientists have classified and quantified goods and services that rivers provide to society. However, they have seldom examined the way in which water management infrastructure and institutional arrangements harness and direct goods and services to different groups in society. Meanwhile, water management paradigms have often considered freshwater ecosystems as rival water users to society or a source of natural hazards and have underplayed the role healthy ecosystems play in providing multiple social and economic benefits. We argue that physical and social structures and processes are necessary to realise multiple benefits from river ecosystems, and that these structures and processes, in the form of (formal and informal) institutions and (grey and green) infrastructure, shape how benefits accrue to different groups in society. We contend that institutions and infrastructure are in turn shaped by political economy. We suggest a more coherent framework for river management research, policy and planning that focuses on a) the ways in which political economy, institutions and infrastructure mediate access and entitlements to benefits derived from ecosystem services, and b) the feedbacks and trade-offs between investments in physical and social structures and processes.